Measuring the capacity of active video games for social interaction: The Social Interaction Potential Assessment tool. (October 2018) - Maitland, Clover; Granich, Joanna; Braham, Rebecca; Thornton, Ashleigh; Teal, Renee; Stratton, Gareth; Rosenberg, Michael
Abstract: Active Video Games (AVGs) have been designed and promoted for family centred leisure in the home. However, few studies have investigated their capacity to facilitate psychosocial outcomes. This study aimed to establish a reliable system to rate the potential of AVGs to facilitate social interaction among players. A conceptual framework was developed to establish the core elements of the Social Interaction Potential Assessment Tool (SIPA). Four raters implemented the SIPA across five AVGs. ANOVAs were conducted to establish the ability of the SIPA to differentiate between AVGs and inter- and intra-rater reliability was tested. The overall SIPA could differentiate between AVG social features. A significant difference was found for Social Facilitators and Pro-social Features, but not for Anti-social Features (p < 0.05). The overall SIPA exhibited excellent inter-rater (ICC = 0.92) and intra-rater (ICCs = 0.95–0.99) reliability. This study identified the core elements of AVGs that enable social interaction. The SIPA tool can assess AVGs' potential to facilitate social interaction among players. Subsequently, the SIPA rating can provide consumers with valuable information on which to base AVG purchasing decisions. Highlights: A framework for the social interaction potential of active video games is presented. The SIPA tool can differentiate between games by social interaction potential. The SIPA tool exhibits excellent inter- and intra-rater reliability. The rating provides valuable information for consumers making purchasing decisions.